2017
DOI: 10.1016/j.fm.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Meat sources of infection for outbreaks of human trichinellosis

Abstract: Trichinellosis is one of the most important foodborne zoonotic diseases, with worldwide distribution. While human risk for trichinellosis has historically been linked to pork, modern pork production systems and slaughter inspection programs have reduced or eliminated pork as a source for trichinellosis in many countries. While pork may no longer pose a significant risk for trichinellosis, many other animal species may be hosts for Trichinella species nematodes and when human consume meat from these animal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 64 publications
1
118
0
1
Order By: Relevance
“…Nevertheless, in general, wild boar, horse, and bear are relatively common nonpork meat sources of trichinosis, whereas although infections from consumption of meat from dog, turtle, jackal, cougar, and walrus have occurred, they are more unusual, presumably because these are less usual meat sources (Rostami et al, 2017). An overview comparison of sources of meat types associated with trichinosis cases and outbreaks divided by region or country (Murrell & Pozio, 2011) indicated that of 27 geographic areas listed, domestic pigs were most associated with trichinosis for 11 of them, but for 13 of these regions wild game was the equivalent or predominant source, with all cases associated with wild game in seven of these regions (Ethiopia, Canada, Iran, Lebanon, Greece, Israel, South Korea).…”
Section: Trichinella Spp: Game Animals Replace Undercooked Pork As Tmentioning
confidence: 99%
“…Nevertheless, in general, wild boar, horse, and bear are relatively common nonpork meat sources of trichinosis, whereas although infections from consumption of meat from dog, turtle, jackal, cougar, and walrus have occurred, they are more unusual, presumably because these are less usual meat sources (Rostami et al, 2017). An overview comparison of sources of meat types associated with trichinosis cases and outbreaks divided by region or country (Murrell & Pozio, 2011) indicated that of 27 geographic areas listed, domestic pigs were most associated with trichinosis for 11 of them, but for 13 of these regions wild game was the equivalent or predominant source, with all cases associated with wild game in seven of these regions (Ethiopia, Canada, Iran, Lebanon, Greece, Israel, South Korea).…”
Section: Trichinella Spp: Game Animals Replace Undercooked Pork As Tmentioning
confidence: 99%
“…Human T. spiralis infection principally results from ingestion of the encapsulated infective larvae present in raw or uncooked meat and meat products. Domestic pigs are the crucial infection source of human T. spiralis infection in China and other developing countries [2][3][4][5]. From 2004 to 2009, 14 trichinellosis outbreaks owing to infected domestic pork and wild boar meat were reported in the Chinese mainland [6].…”
Section: Introductionmentioning
confidence: 99%
“…From 2004 to 2009, 14 trichinellosis outbreaks owing to infected domestic pork and wild boar meat were reported in the Chinese mainland [6]. As a considerable quantity of pork is consumed around the world, T. spiralis infection in domestic pigs represents a severe risk to public health and a notable hazard to pork meat safety [5,7]. Therefore, it is necessary to develop a preventive vaccine to block Trichinella infection in domestic swine and transmission from swine to humans [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Trichinella spp., pathogenic agents of trichinellosis, are foodborne zoonotic nematodes that can infect more than 100 species of mammals, birds and reptiles (Gottstein, Pozio, & Nöckler, ; Pozio, ). Humans can acquire infection with T. spiralis through ingestion of raw or undercooked meat from domestic (pigs, horses) and wild animals (wild pigs, bears) that contaminated with the muscle larvae (ML) of T. Spiralis (Rostami, Gamble, Dupouy‐Camet, Khazan, & Bruschi, ). Trichinellosis poses a worldwide public risk of human and animal health (Cui, Wang, & Xu, ; Pozio, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pork consumption holds the highest rate out of all terrestrial animals by humans and will continue to grow in future (Pozio, ). Meanwhile, the domestic pork and pork‐related products also act as main sources of human acquired T. spiralis infection (Pozio, ; Rostami et al., ). Despite the trichinellosis burden has been significantly reduced in pigs under industrial farming conditions that are only responsible for more than half of the global pig production, the circulation of Trichinella spp.…”
Section: Introductionmentioning
confidence: 99%